PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DI SMA NEGERI 1 PERCUT SEI TUAN TAHUN AJARAN 2025/2026 - Sayyidina; Eko Wahyu Nugrahadi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to determine the effect of the Game Based Learning model on students' learning outcomes in Economics subjects for Grade X students at SMA Negeri 1 Percut Sei Tuan in the 2025/2026 academic year. This research employed a quasi-experimental method using a pretest-posttest control group design. The population consisted of 356 Grade X students from 10 classes, while the sample included class X-1 as the experimental class and class X-2 as the control class, each consisting of 36 students. Data were collected through observation, interviews, documentation, and tests. Data analysis was conducted using normality tests, homogeneity tests, and hypothesis testing through the Independent Sample T-Test. The results showed that the average posttest score of the experimental class was 86.11, which was higher than that of the control class at 72.56. The hypothesis test yielded a significance value of 0.000 < 0.05, indicating that Ha was accepted and H0 was rejected. These findings demonstrate that the Game Based Learning model has a significant effect on students' learning outcomes. Therefore, the implementation of the Game Based Learning model can be considered an effective alternative for improving students' learning outcomes in Economics subjects. Keywords: Game Based Learning; Learning Outcomes; Economics Education; Quasi Experiment; Innovative Learning.   Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Game Based Learning terhadap hasil belajar siswa pada mata pelajaran Ekonomi kelas X di SMA Negeri 1 Percut Sei Tuan Tahun Ajaran 2025/2026. Penelitian ini menggunakan metode quasi experiment dengan desain pretest-posttest control group design. Populasi penelitian berjumlah 356 siswa kelas X yang terdiri dari 10 kelas, sedangkan sampel penelitian adalah kelas X-1 sebagai kelas eksperimen dan kelas X-2 sebagai kelas kontrol yang masing-masing berjumlah 36 siswa. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dokumentasi, dan tes. Analisis data menggunakan uji normalitas, uji homogenitas, dan uji hipotesis (Independent Sample T-Test). Hasil penelitian menunjukkan bahwa rata-rata nilai posttest kelas eksperimen sebesar 86,11 lebih tinggi dibandingkan kelas kontrol sebesar 72,56. Hasil uji hipotesis memperoleh nilai signifikansi sebesar 0,000 < 0,05, sehingga Ha diterima dan H0 ditolak. Temuan ini menunjukkan bahwa model pembelajaran Game Based Learning berpengaruh signifikan terhadap hasil belajar siswa. Dengan demikian, penerapan model pembelajaran Game Based Learning dapat menjadi alternatif yang efektif dalam meningkatkan hasil belajar siswa pada mata pelajaran Ekonomi. Kata Kunci: Game Based Learning; Hasil Belajar; Ekonomi; Quasi Experiment; Pembelajaran Inovatif.